2019
DOI: 10.1002/ange.201813895
|View full text |Cite|
|
Sign up to set email alerts
|

Efficient Homogeneous Electrocatalytic Water Oxidation by a Manganese Cluster with an Overpotential of Only 74 mV

Abstract: Water electrolysis is among the simplest method for generating hydrogen as an alternative renewable fuel. A major challenge associated with this process is the development of cheap, simple, and environmentally benign catalysts that lead to a minimum overpotential for water oxidation. Inspired by the Mn4CaOx cluster that catalyzes water oxidation in photosystem II, described here is the synthesis and characterization of the manganese cluster [Mn12O12(O2CC6H2(OH)3)16(H2O)4] (Mn12TH) along with its electrocatalyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 78 publications
0
4
0
Order By: Relevance
“…Recently, the widely explored methods for designing good OER electrocatalysts are focused on building more surface sites for water adsorption and dissociation, , which happens in the surface double electrode layer (DEL). To date, we have reported that the additional 3d empty electronic orbitals of tungsten enhance water adsorption, and the solid/solution interface resistance of the corresponding DEL is reduced, which then lowers the water oxidation overpotential .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the widely explored methods for designing good OER electrocatalysts are focused on building more surface sites for water adsorption and dissociation, , which happens in the surface double electrode layer (DEL). To date, we have reported that the additional 3d empty electronic orbitals of tungsten enhance water adsorption, and the solid/solution interface resistance of the corresponding DEL is reduced, which then lowers the water oxidation overpotential .…”
Section: Introductionmentioning
confidence: 99%
“…1D exhibited a broad peak between 30 and 40 degrees of the 2y value, which indicated the different diffraction peaks of Co 0.45 S 0.38 Se 0.17 compared with standard CoS 2 (PDF # 41-1471; a = b = c = 5.5376 Å; space group: Pa3), and the different diffraction peaks corresponding to the standard CoSe 2 (PDF # 09-0234; a = b = c = 5.8588 Å; space group: Pa3). 50,51 The binary CoSe 2 nanosheets nearly have the same diffraction peaks as the CoSe 2 cubic crystals.…”
Section: Resultsmentioning
confidence: 92%
“…We have carried out the quantitative H 2 evolution experiment in a homemade electrochemical cell (three-electrode system) to measure the H 2 gas produced by compound 1 during the CPE experiment at a constant potential of −0.53 V versus RHE. We have thereby calculated the Faradaic efficiency of compound 1 for the HER, which was found to be 88.6%, as shown in Figures S15–16 and Section S5 (SI). , …”
Section: Resultsmentioning
confidence: 99%
“…We have thereby calculated the Faradaic efficiency of compound 1 for the HER, which was found to be 88.6%, as shown in Figures S15−16 and Section S5 (SI). 59,60 In order to understand the HER kinetics of compound {Mn 0.03 Na 0.01 }@[Mo 0.93 VI Mo 0.07 V O 3 ] (1), EIS studies were carried out. As shown in Figure S17 (SI), compound 1 shows a lower charge transfer resistance value (R ct = 82.72 Ω) as compared to the blank glassy carbon electrode (157.10 Ω), as estimated from the semicircles in the high-frequency range of the Nyquist plots.…”
Section: ■ Introductionmentioning
confidence: 99%